Birth weight, childhood size, and muscle strength in adult life: evidence from a birth cohort study. - Kuh, D; Bassey, J; Hardy, R; Aihie Sayer, A; Wadsworth, M; Cooper, C (2002)
Environmental influences during gestation may have long-term effects on adult muscle strength. It is not known how early in adult life such effects are manifest and whether they are modified by childhood body size. The authors examined the relation between birth weight and hand grip strength in a prospective national birth cohort of 1,371 men and 1,404 women from the Medical Research Council National Survey of Health and Development who were aged 53 years in 1999. A positive relation between birth weight and adult grip strength remained after adjustment first for adult height and weight and then additionally for childhood height and weight (p = 0.006 for men and p = 0.01 for women). The effects of birth weight on grip strength did not vary by childhood or current body size and were not confounded by social class. To the authors' knowledge, this is the first study to show that birth weight has an important influence on muscle strength in midlife independent of later body size and social class. It suggests that birth weight is related to the number of muscle fibers established by birth and that even in middle age compensating hypertrophy may be inadequate. As the inevitable loss of muscle fibers proceeds in old age, a deficit in the number of fibers could threaten quality of life and independence.